Horns Up! The Integration of Heavy Metal Music as a Motivational Technique for Teaching English as a Foreign Language: A Systematic Literature Review - Romero-Argueta, Jesús (International Journal of Humanities, Education, and Social Sciences, 2025)
This systematic literature review explores the integration of Heavy Metal music as a motivational tool in teaching English as a Foreign Language (EFL), addressing an innovative yet underexplored area within pedagogical research. Drawing on three peer-reviewed studies published between 2020 and 2025 and selected through the PRISMA framework, the review examines pedagogical strategies, educational benefits, and implementation challenges associated with using Heavy Metal music in EFL classrooms. The analysis reveals that Heavy Metal’s rich lexical content, rhythmic complexity, and cultural resonance significantly enhance learner engagement, vocabulary acquisition, and phonological awareness—particularly among advanced learners at B2 to C2 levels of the CEFR. Additionally, its emotionally expressive lyrics and dynamic musical structure contribute to a low-anxiety, inclusive classroom environment, supporting principles of culturally responsive teaching. Despite these advantages, barriers such as limited empirical research, the lyrical complexity of the genre, and the lack of structured pedagogical models impede broader adoption. The review highlights the need for longitudinal studies, genre-specific frameworks, and investigations into learner diversity to better understand the long-term effects and practical applications of this approach. Overall, the findings offer evidence-based insights for educators aiming to implement innovative, student-centered strategies that leverage the motivational potential of Heavy Metal music to enrich EFL instruction.